Pig keeping in Northeast India - International Livestock Research Institute (International Livestock Research Institute, 2008)
As demand for pork skyrockets in India, traditional smallholder pig keepers in remote northeast regions of the country could benefit if provided with improved animal feeds, veterinary and other services, allowing them to enter the vibrant new markets.